PENGARUH SELF-EFFICACY DAN COPING TERHADAP PERILAKU ASSERTIF MAHASISWA - Sri Ngayomi Yudha Wastuti; Feri Haryati (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
This research is based on the assumption that there is a relationship between self-efficacy and coping on student behavior. This study uses a correlational quantitative type approach. The population in this study was 142 people, and samples were taken using Simple Random Sampling of 60 people. The data analysis technique uses product moment correlation and multiple linear regression. The results showed that the variables of self-efficacy and coping had a joint effect on student behavior.